User Classification and its Applicability for the Purposes of Game-Based Learning Development - Nowacki, Filip; Ryfa, Jakub (Studia Oeconomica Posnaniensia, 2015)
In recent years the increasing importance of using games in higher education and business training courses has been observed. This is due to their applicability as educational tools that provide a new method of knowledge transfer. Consequently, educational games cannot be compared with other advanced and popular entertainment games. The article describes the differences between various types of games in order to present the possibilities for their use in the teaching process, among other things. It also explains the effectiveness of one particular game-based learning method for educational purposes. The main aim of the article is to present a theoretical analysis of knowledge regarding the innovative aspects of competition (otherwise gamification); focusing on game-based learning and presenting different types of potential users. This may be particularly useful for game designers seeking to attract diverse groups of users. As a result this should lead to the development of more engaging educational games, with particular emphasis on their successful application in the teaching process.